PRESENTATION DOSSIER “Cultural & Technological Images” - Araújo, Denize (Animus. Revista Interamericana de Comunicação Midiática, 2021)
The Dossier “Cultural & Technological Images” presents ten texts by authors from ten different countries who discuss contemporary aspects that deal with images in their cultural environments and/or in their technological productions. Five texts are in English and five in Spanish. The Dossier is a publication of the VIC- Visual Culture WG, one of the Working Groups of the IAMCR – International Association for Media and Communication Research, which receives proposals from 98 countries for its Annual Conferences. On behalf of VIC, I thank the editors of ANIMUS, who are kindly publishing the Dossier in their relevant journal whose proposal is to promote research and production in the area of Communication accepting academic works in Portuguese, Spamish and English in themes belonging to journalism, publicity, cinema and audiovisual, as well as themes that develop interfaces with Communication.